AUTOMATIC TAG CLOUD GENERATION FROM TURKISH CONTENTS - Savasan, Serdar; Diri, Banu (YILDIZ TECHNICAL UNIV, 2011)
Every day we are faced with an intense traffic of information that is caused by the communication medium, shaping by the growth and development of information technologies and the Internet. Users can access to information in a more comfortable way by the help of text summarization, information extraction and document tagging operations. Tag clouds are visual tools that direct users to the information provided on the internet by taking advantage of text mining techniques. Generally the users prefer to follow the agenda from a single newspaper web site. But a large number of unimportant news items that are not published in newspaper printed version, find place for themselves on internet sites and cause information pollution. Considering the needs posed by these and other problems, a research on information retrieval systems, text mining and tag clouds, has been made in this study. With the aid of gathered information, a news compilation and retrieval tool called Agenda Cloud is developed, which makes it more functional to access news on the Internet. The main benefits of the application are; it allows users to access a lot of information in a short amount of time and provides historical information besides daily agenda.
Keywords: Information retrieval systems; text mining; text analysis; tag cloud; collecting news compilation; document tagging; Engineering